Quantitative Determination of ABT-925 in Human Plasma by On-Line SPE and LC-MS/MS: Validation and Sample Analysis in Phase II Studies - Katty Wan; Matthew Rieser; Tawakol El-Shourbagy (MDPI AG, 2010)
A fully automated 96-well On-Line Solid Phase Extraction (SPE) followed by High Performance Liquid Chromatography (HPLC)-Tandem Mass Spectrometric (MS/MS) method for the determination of ABT-925 (2-{3-[4-(2-tert-Butyl-6-trifluoromethyl-pyrimidin-4-yl)-piperazin-1-yl)-propyl-sulfanyl}-3H-pyrimidin-4-one fumarate) in human plasma was developed, validated and utilized in Phase II clinical studies. 50 µL of plasma sample was fortified with internal standard (IS, d8-ABT-925) and extracted on-line with Cohesive Turbo Flow Cyclone P HTLC column. The chromatographic separation was performed on Aquasil C18 (3 μm 50 × 3 mm) HPLC column with a mobile phase consisting of 50/50/0.1 (v/v/v) ACN/H2O/formic acid. The mass spectrometric measurement was conducted under positive ion mode using multiple reaction monitoring (MRM) of m/z 457.4 → 329.4 for analyte and m/z 465.5 → 337.5 for IS.The peak area ratio (analyte/IS) was used to quantitate ABT-925. A dynamic range of 0.0102 μg/mL to 5.24 μg/mL was established after the validation. The validated method was then used for two Phase II studies. To demonstrate the method reproducibility, approximately 10% of the incurred samples from one study were repeated in singlet. The repeated values were compared to the initial values. All repeated values agreed within ±15% of the mean values.